Vladimir Bibikhin’s Ontological Hermeneutics - Mikhailovsky, Aleksandr (Stasis, 2015)
This article examines Vladimir Bibikhin‘s recently published series of lectures, Property. Philosophy of the Self, which he delivered at Moscow’s Lomonosov University in 1993–1994. In it, he creatively develops Heidegger’s project of “phenomenological destruction”: a critical analysis of the traditional arsenal of classical ontology and modern European philosophy (substantialism and subjectivism) guided by the question of being and working through a new reading of classical thought (Alcibiades I). The command “Know thyself” demands we address the question of one’s own selfhood, that which is proper to the self—a direct a priori given of human existence. In Bibikhin’s definition of “one’s own,” primary importance is allotted not to the “private self” (with its engagement with inner worldly things), but to the relationship with the whole world, out of which the emergence of the subject is made possible for the first time. The article analyzes the original interpretations of concepts Bibikhin puts forth in his philosophy, such as “property,” “world,” and “capture”.